PERANCANGAN DAN PENGEMBANGAN APLIKASI WEB PENJUALAN (Studi Kasus : CV. Herson Mitra Solusindo) - Muhammad Sony Maulana (Universitas Bina Sarana Informatika, 2014)
AbstractWeb-based applications is a solution of doing business today. The web application can run on all operating systems such as Windows, Linux and Mac OS. The web application can be accessed only by using a browser and does not require specification of a computer that is too high. Good sales application is an application that can display data sales transaction and sales reports to calculate profit and loss as a measure of the progress of the company. These data should be presented in realtime, although periodically and safely accessed simultaneously by multiple users. Web applications have a minimum of three sales of the super admin user, manager and cashier, cashier and manager which is a derivative of the super admin. Web applications that run online sales can facilitate the owners of the company in managing the company.Keywords: companymanaging, web based applications